2008
DOI: 10.1111/j.1440-6055.2008.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

The mortality of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) neonate larvae in relation to drop‐off and soil surface temperature: the dangers of bungy jumping

Abstract: The first larval instar has been identified as a critical stage for population mortality in Lepidoptera, yet due to the body size of these larvae, the factors that contribute to mortality under field conditions are still not clear. Dispersal behaviour has been suggested as a significant, but ignored factor contributing to mortality in first-instar lepidopteran larvae. The impact that leaving the host plant has on the mortality rate of Helicoverpa armigera neonates was examined in field crops and laboratory tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 31 publications
(52 reference statements)
1
34
0
Order By: Relevance
“…The Bt‐susceptible larvae moving off plant parts with high Bt content may encounter less toxic plant parts. Helicoverpa armigera larvae are likely to re‐establish on a plant if they drop to the ground within 5 cm of the stem (Perović et al, ). They have been able to survive off the plant for at least 1 h, and travel up to 80 cm from where they dropped to the ground (for a similar finding see Terry et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Bt‐susceptible larvae moving off plant parts with high Bt content may encounter less toxic plant parts. Helicoverpa armigera larvae are likely to re‐establish on a plant if they drop to the ground within 5 cm of the stem (Perović et al, ). They have been able to survive off the plant for at least 1 h, and travel up to 80 cm from where they dropped to the ground (for a similar finding see Terry et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Helicoverpa armigera larvae were found to drop off more often from WT plants induced with mites than from plants induced by caterpillar feeding or from non-induced plants. We have shown that H. armigera larvae do not survive long on the ground (Perovic et al, 2008). However, in contrast, a higher percentage of neonate fall armyworms Spodoptera frugiperda (JE Smith) remained on herbivore-induced cowpea seedlings [Vigna unguiculata (L.) Walpers] (Carroll et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Transfer was done by catching their silk using a fine camel-hair brush and allowing them to drop onto the plant surface, thus mimicking natural drop-off behaviour (Perovic et al, 2008), avoiding damaging the larvae and disturbing their behaviour. All larvae used in these studies were newly hatched.…”
Section: Arthropod Culturesmentioning
confidence: 99%
“…• C the eggs were laid on a leaf [18][19][20][21][22][23]. 90% of eggs were hatched at 200 W and 76% eggs hatched at 250 W after the exposure.…”
Section: Mature Tomatomentioning
confidence: 99%